Kabi Kumudarañjana janmaśatabārshikī smāraka grantha - Mallika, Kumudarañjana, 1883-1970 (Kabi Kumudarañjana Janma-Śatabārshikī Samiti : prāptisthāna Granthagorha, 1983)
Birth centennial volume for Kumudarañjana Mallika, 1883-1970, Bengali poet; comprises articles on his life and works, and a selection of his works and letters.